Learning Happiness Supporting Factors for Bangpleeratbamrung School Students, Bang Phli District, Samut Prakan Province - Sawetwisut, Napitchanun; Koolnaphadol, Pennapha (STOU Academic Journal of Research and Innovation (Humanities and Social Science), 2026)
This research aimed to study the factors that promote happiness in learning of lower secondary school students at Bangplee Rat Bamrung School, Bangplee District, Samut Prakan Province. The sample group used in this research was lower secondary school students at Bangplee Rat Bamrung School, Bangplee District, Samut Prakan Province, academic year 2024, totaling 686 people using the sample size determination according to the table of Krejcie and Morgan (1970). The research instrument was questionnaire. Data were analyzed using percentages, means, and standard deviations. The research results found that there were 4 factors that promoted happiness in learning in this study as follows: 1) Each child was accepted by friends and teachers; 2) Teachers were kind, sincere, and gentle to all children; 3) Children loved and were proud of themselves; and 4) Each child had the opportunity to choose to study according to their abilities and interests. Overall, the factors that promoted happiness in learning were all at a moderate level ( = 3.23, S.D. = 0.26). When considering each aspect, it was found that Factors that promote happiness in learning in aspect 4) Each child has the opportunity to choose to study according to their aptitude and interests at a high level ( = 3.91, S.D. = 0.29), followed by aspect 1) Each child is accepted by friends and teachers at a moderate level ( = 3.01, S.D. = 0.25), aspect 2) Teachers are kind, sincere, and gentle to all children at a moderate level ( = 3.26, S.D. = 0.24), and aspect 3) Children have love and pride in themselves at a moderate level ( = 2.76, S.D. = 0.29). The results of this study can be used as basic information for teachers and educational personnel to be a guideline for promoting happiness in learning effectively in the future.